Optimal Contracting with Endogenous Project Mission - Lea Cassar (Center for Economic Studies and ifo Institute (CESifo), 2016)
I analyze a model in which a principal offers a contract to an agent and can influence the agent's marginal return of effort by the choice of the project mission. The principal's and the agents' mission preferences are misaligned, and the agents have unobservable intrinsic motivation levels. I show that the non-contractibility of effort (asymmetric information) brings the mission closer to the agent's (principal's) preferences. Furthermore, when effort is non-contractible, the optimal mechanism i) has a “double distortion”' in the mission; ii) does not exclude low-types agents; and iii) can be implemented through a scoring auction. Several applications are discussed.
Keywords: H41; D23; D82; M52; 330; optimal contracting; non-monetary incentives; mission preferences; intrinsic motivation